2004
DOI: 10.1074/jbc.m408883200
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Transcription Complexes to the β-Globin Gene Locus in Vivo and in Vitro

Abstract: Erythroid-specific, high level expression of the ␤-globin genes is regulated by the locus control region (LCR), composed of multiple DNase I-hypersensitive sites and located far upstream of the genes. Recent studies have shown that LCR core elements recruit RNA polymerase II (pol II). In the present study we demonstrate the following: 1) pol II and other basal transcription factors are recruited to LCR core hypersensitive elements; 2) pol II dissociates from and re-associates with the globin gene locus during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 42 publications
(47 reference statements)
9
76
0
Order By: Relevance
“…Moreover, Pol II occupancy at the promoter decreased 30-40% in p45/NF-E2-null mice, whereas Pol II occupancy at the LCR remained unchanged (Kooren et al, 2007). Biochemical analysis supports the feasibility of long-range Pol II transfer (Vieira et al, 2004).…”
Section: P45/nf-e2supporting
confidence: 48%
“…Moreover, Pol II occupancy at the promoter decreased 30-40% in p45/NF-E2-null mice, whereas Pol II occupancy at the LCR remained unchanged (Kooren et al, 2007). Biochemical analysis supports the feasibility of long-range Pol II transfer (Vieira et al, 2004).…”
Section: P45/nf-e2supporting
confidence: 48%
“…LCRs may recruit transcription factors and components of the transcription preinitiation complex, including RNA polymerase II, that are subsequently transferred to the promoter region (25,32,47). Our finding that Pol II is bound to HS3 in the 5Ј HS cluster and the promoter region in WT mast cells and BMMC isolated from W sh/sh and BAC200-Kit-GFP transgenic mice, but not in the promoter of the GFP-negative BMMC isolated from W sh/sh , BAC30-Kit-GFP, and BAC200-⌬5ЈHS-Kit-GFP mice, is consistent with such a mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…RNA polymerase II has been reported to associate with distal upstream transcriptional control elements in several model systems (25,42,47). A long-range transfer mechanism in which Pol II is first recruited to the upstream regulatory element and then transferred to the promoter has been proposed.…”
Section: T39 and T71) And Two Lines With Bac200⌬5јhs-kit-gfp (T78 Amentioning
confidence: 99%
“…Previous studies have shown that Pol II interacts with LCR HS2 and with the adult β-globin gene promoter and that the binding increases on induction of MEL cell differentiation (26)(27)(28)(29). As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%